Islamic Literacy Education as An Effort to Prevent Bullying at Muhammadiyah Junior High School Suradadi Tegal - Azami, Tomi; Nurhayati, Sri Adi; Azizah, Nurul; Haqqi, Abdurrahman Raden Aji (Belajea: Jurnal Pendidikan Islam, 2025)
A series of bullying incidents in the school environment is increasingly concerning. Bullying involving students has now reached the junior high and even elementary school levels. The purpose of this study is to describe and analyze the implementation of bullying prevention strategies at Muhammadiyah Junior High School Suradadi Tegal. This study specifically investigates the integration of Islamic literacy within a comprehensive bullying prevention framework. The study uses a qualitative approach with a case study research design. The informants were selected using purposive sampling, based on criteria determined by the researcher. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive analysis techniques. The findings show that the implementation strategy for bullying prevention through the integration of Islamic literacy at Muhammadiyah Junior High School Suradadi Tegal was carried out in several ways: (1) Formulating policies related to bullying; (2) Promoting the concept of Child-Friendly Schools (CFS); (3) Collaborating with external parties; (4) Hidden curriculum; (5) Internalization of Islamic Literacy. The unique finding of this study is that bullying prevention strategies are not only based on formal policies but are also strengthened through the internalization of Islamic literacy into school culture, such as using the slogan fastabiqul khoirat, the morning greeting habit, and external collaborations that foster empathy and equality among students.